Outcomes of Surgery for Benign Tumours in The Upper Extremity - Zyluk, Andrzej; Owczarska, Ada (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2023)
Benign tumours of the upper extremity are common in hand surgeons’ practice. The most commonly diagnosed are giant-cell tumours of the tendon sheath and lipomas.The objective of this study was an investigation into the distribution of tumours in the upper limb, their symptomatology and outcomes of surgery, particularly regarding the rate of recurrence.Material and Methods A total of 346 patients, 234 women (68%) and 112 men (32%), who had undergone surgery for tumours located in the upper extremity which were not ganglion cysts were enrolled into the study. The follow-up assessment was performed at a mean of 21 months (range 12–36) post-operatively.Results The most common tumour in this study was giant cell tumour of the tendon sheath − 96 cases (27.7%), followed by lipoma − 44 cases (12.7%). Most lesions − 231 (67%) were localized in the digits. A total of 79 (23%) recurrences were noted, the most common after surgery for rheumatoid nodules - 43.3% and the giant-cell tumours of the tendon sheath − 31.3%. The independent factors increasing risk of recurrence following the tumour’s resection were: histological type of the lesion - the giant-cell tumour of the tendon sheath (p=0.0086) and the rheumatoid nodule (p=0.0027), as well as a combination of incomplete (non-radical) and not “en block” resection of tumours. A brief review of the literature referring to the presented material is offered.
Keywords: benign hand tumours; risk of recurrence